Marketing Performance of “Pelanusa” Patchwork Products in This Era 5.0 - Widiya Dewi Anjaningrum; Fransiska Sisilia Mukti; Agus Purnomo Sidi (Proceeding of The International Conference on Economics and Business, 2022)
Pelanusa Group, a group of patchwork craftswomen based on social entrepreneurship, has been facing a drastic decline in market performance for its creative products since the occurrence of disruptive technology accelerated by the Covid-19 outbreak. The purpose of this study is to determine the role of digital platforms and e-commerce marketing capabilities in building marketing innovation capabilities that have an impact on marketing performance. A total of 160 Pelanusa patchwork craftsmen have been selected as respondents using purposive sampling technique. The data collected through the questionnaire was analyzed with SmartPLS 4.0.7.8 Software. The results of the study show that there is a very important role in the use of digital platforms and mastery of e-commerce marketing because these two things will be able to break the ability of innovation in marketing. Strong marketing innovation will have an impact on marketing performance as indicated by expanding market share and increasing customer satisfaction as well as total sales. It is recommended that further research be able to reveal digital marketing strategies that can be applied by craftswomen and people with disabilities so that they can remain productive at work and have income from selling their products.